Answer:
3
Step-by-step explanation:
Three times three equals nine. Or you can just go by one times one, two times two, three times three.
Answer:
x>-6
Step-by-step explanation:
The expression you need to solve for this is: 2x+15>3
For now pretend that the > is a = and solve as you normally would for x.
Subtract 15 from both sides
2x=-12
Divide by 2
x=-6
Put the > back in
x>-6
Answer:
Step-by-step explanation:
-10 ( y-4) + 3y = 5 <--- substitute the value of x into first equation
-10y + 40 + 3y = 5
-7y + 40 = 5
-7y = -35
y= 5
x = 5 - 4
x = 1